Pengaruh Terapi Perilaku Kognitif terhadap Kemampuan Interaksi Sosial pada Klien Isolasi Sosial di Provinsi Bengkulu - Shinta Shinta (JURNAL KEPERAWATAN MUHAMMADIYAH BENGKULU, 2019)
Social isolation is a condition of isolation from someone with schizophrenia so that the ability to interact with others decreases to be something negative. This study aims to determine the effect of cognitive behavioral therapy on the social interaction ability of social isolation clients in Bengkulu Province. The research method, this research is a quantitative study using a Quasi Experiment research design with a pre test and post test approach design without control group. The sample of this study was 30 people with total sampling techniques. The results of the study of social interaction ability of patients social isolation seen from the variables of cognitive abilities, affective and behavior. The average cognitive ability before giving therapy is 13.79, while after therapy is 19.88. The average affective ability before therapy was 14.58 while after therapy was 17.33. The average behavioral ability before therapy is 9.64 while after therapy is an average of 11.06. Based on the results of the t-dependent test, there were differences in the average score before and after the administration of Cognitive Behavior therapy, with the Ï value of each variable 0,000 (Î± = 0.05). Conclusion, Cognitive Behavior therapy has a significant effect on the ability of social interactions of social isolation patients in Bengkulu Province. Cognitive behavioral therapy is recommended as nursing therapy in treating social isolation clients with decreased social interaction abilities.Â Keywords: Cognitive behavioral therapy, Social interaction ability, Client social isolation